Social Europe. Aiming for inclusive growth - Annual report of the Social Protection Committee on the social situation in the European Union (2014) (Luxembourg, 2015)
"The report delivers on the core task of the Social Protection Committee (SPC) to monitor the social situation in the Member States and the European Union. It is prepared by the Secretariat of the Committee and its Indicators' Sub-group. The report provides an analysis of recent trends in the social situation in the Member States and the European Union and shows that there has been little improvement in the overall situation in the EU, although trends are more mixed than in preceding years. Continuing disparities occur across Member States and the situation is worsening in several. The report focuses on the results from the latest edition of the Social Protection Performance Monitor (SPPM), which is based on a set of key indicators for monitoring developments in the social situation.